Approcci metodologici e indicazioni progettuali per il restauro del Palazzo del Doge ad Antivari, Montenegro. - Cardaci, Alessio; Versaci, Antonella (Restauro Archeologico, 2016)
The restoration project of an old building requires an approach based on the capacity of the designer to build a computational model that interprets its constructive history. The Doge’s Palace in Antivari a millenary citadel of Montenegro, results from several construction phases that cannot be properly explained only through the application of mechanics principles. The integrated survey and elevation’s stratigraphic study, important to the archaeologist and the architect for the reconstruction of the building’s evolutionary phases, are to the engineer a necessary tool for understanding the structure’s static and dynamic behaviour. This work addresses the issue of the protection of archaeological sites and investigates the means of intervention on buildings in a state of ruin, choosing to run a project of ‘authentic restoration’ that, by establishing structure’s collapse mechanisms, is oriented on non-invasive/removable solutions, designed to not alter the building’s identity.